2016
DOI: 10.3906/tar-1506-39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water regimes on inulin content and inulin yield of Jerusalem artichoke genotypes with different levels of drought tolerance

Abstract: Drought is a major problem for Jerusalem artichoke production in rainfed areas, as it reduces inulin accumulation in tubers (Conde et al., 1991;Schittenhelm, 1999;Monti et al., 2005). Under rainfed conditions, drought greatly reduced stalk dry weight, tuber dry weight, sugar yield, and inulin yield of Jerusalem artichoke, and differential responses of Jerusalem artichoke genotypes to drought for these characters were observed (Kocsis et al., 2007(Kocsis et al., , 2008. A supply of 50% of the water requirement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Results in Table 7 show that irrigated artichoke plants with 75 and 100% ETc magnetized water at produced the highest inulin content in edible part of heads in both seasons. Results are in harmony with those obtained by (Aduldecha et al, 2016) reported that inulin production was significantly reduced by low soil moisture content, and the decline was particularly noticeable under extreme drought stress, also, (Tartoura et al, 2020) found that irrigation with magnetized water gave the highest values of inulin compared with control non-magnetized water treatment on Jerusalem artichoke plants. Fertilizing with 100 NPK produced the highest values of inulin content in total heads with no significant differences with fertilizing with 75% of recommended dose in both seasons Table 7.…”
Section: Chemical Components Dry Matter (%)supporting
confidence: 88%
“…Results in Table 7 show that irrigated artichoke plants with 75 and 100% ETc magnetized water at produced the highest inulin content in edible part of heads in both seasons. Results are in harmony with those obtained by (Aduldecha et al, 2016) reported that inulin production was significantly reduced by low soil moisture content, and the decline was particularly noticeable under extreme drought stress, also, (Tartoura et al, 2020) found that irrigation with magnetized water gave the highest values of inulin compared with control non-magnetized water treatment on Jerusalem artichoke plants. Fertilizing with 100 NPK produced the highest values of inulin content in total heads with no significant differences with fertilizing with 75% of recommended dose in both seasons Table 7.…”
Section: Chemical Components Dry Matter (%)supporting
confidence: 88%
“…Likewise, the inulin content in collections of wild dahlia (Dahlia coccinea) ranged between 23.9-42.5 g/100 g (Santana et al, 2016), however, when these plants were cultivated, their concentration increased significantly. These results suggest that the inulin concentration is associated with genetic, physiological and environmental factors (temperature and photoperiod) (Başaran et al, 2017), without considering the changes suffered by the root over time, due to the fact that as the roots get older, they accumulate reserves in the form of inulin and longer-chain fructans (Aduldecha et al, 2016).…”
Section: Physicochemical Qualitymentioning
confidence: 96%
“…Genotypes, JA5, JA125 and JA60 were tolerant to severe drought and recommended for drought conditions. Another genotype, HEL65, gave high inulin content under field capacity water levels and tolerated moderate drought, showing high inulin content under 50% and 25% of soil available water [3]. The positive qualities of this genotype should be developed by breeding.…”
Section: Introductionmentioning
confidence: 99%